Psychometric properties of the Recovery Experiences Questionnaire in Argentine workers. - Trógolo, Mario; Morera, Luis; Castellano, Estanislao Joaquín; Spontón, Carlos; Medrano, Leonardo Adrián (Anales de Psicología / Annals of Psychology, 2020)
The aim of this study was to examine the psychometric properties of the Recovery Experience Questionnaire in Argentina. Five-hundred and five workers from public, private and non-governmental sectors participated in the study. Confirmatory factor analysis showed that the four-factor model has acceptable fit to the data. Thus, as the original scale, the Argentinean validation maintain the four recovery experiences—psychological detachment from work, relaxation, mastery experiences and control over leisure time. Reliability analyses showed good internal consistency (Cronbach’s α ranging from .75 to .92) and construct reliability (coefficient H ranging from .88 to .93) for all subscales. Correlations theoretically expected with measures of work engagement, burnout and negative affect supported for concurrent validity. Thus, the Recovery Experience Questionnaire shows adequate psychometric properties for its use in Argentina, make available a reliable instrument that allows deepening knowledge about recovery and providing a valuable tool for professional practice.